MOTIVATION, SKILLS AND ENTREPRENEURIAL SPIRIT AS THE MAIN CAPITAL OF CHARACTER BUILDING BECOME "SCHOOL AGE MASTERS" (JUS) IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Ai Nurhayati; Sri Widawati; Teti Sobari (JLER (Journal of Language Education Research), 2019)
This research is motivated by the increasing prevalence of school-age adolescents who become entrepreneurs, both online and offline, entrepreneurial spirit, and skills possessed by teenagers need to get motivation or motivation, with this research expected to shape the character of young entrepreneurs in school age used in this study is descriptive qualitative, namely finding and knowing the facts that occur related to adolescents to be eunterreunerers at school age, by interviewing, documenting and observation, because based on data while 60% of school students have entrepreneurship, the solution to this problem is forming the character of entrepreneurial spirit to become a "skipper at school age" by providing motivation and skill to become an eunterreuner. Then learning Entrepreneurship so that the entrepreneurial spirit in adolescents can be channeled even though it is in public and not a vocational school so that unemployment at a young age can be overcome and can compete in the industrial era 4.0.